ПРОБЛЕМА ВИЗНАЧЕННЯ КОМПЕТЕНТНОСТЕЙ ВЧИТЕЛЯ ТЕХНОЛОГІЙ ДЛЯ ЗДІЙСНЕННЯ ЕФЕКТИВНОЇ ПЕДАГОГІЧНОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2009)
In article the definition problem competence teachers of technologies with which help probably to provide not only the international recognition of diplomas, and a recognition of their professional suitability has been opened.